The Influence of Marketing Strategy on SME Performance in the Global Market Mediated by Competitive Advantage - Yandi Suprapto; Caroline Angelina; Wisnu Yuwono (UNIVED Press, 2025)
This research examines the direct and indirect influence of marketing intelligence, product innovation, and pricing on the performance of SMEs in Batam City through competitive advantage. Using a sample of 195 fashion SMEs in Batam, researchers used the partial Least Squares (PLS) structural equation modeling method to analyze. The results show that marketing intelligence, product innovation, and pricing significantly contribute to competitive advantage and SME performance. The results of the mediation test show that competitive advantage is proven to mediate marketing intelligence on SME performance and competitive advantage is not proven to mediate product innovation and pricing on SME performance. These findings have an important impression on SMEs and startups who are interested in developing or exploiting opportunities in the global market.